STRESS AND RESILIENCE AMONG EFL TEACHERS: AN INTERVIEW STUDY OF AN INDONESIAN JUNIOR HIGH SCHOOL TEACHER - Rizqi, M. Ainur (TEFLIN Journal, 2017)
While stress remains a classic problem in teaching, the concept of resilience is central to help teachers find the joy of their teaching and make them stay longer at the job. This study involved one EFL teacher who had more than a five years' teaching experience, and was regarded as capable, not only of maintaining her positive commitment, but also of demonstrating exceptional achievement during her career thus far. An in-depth semistructured interview was conducted with these two key aims: (1) to identify sources of stress that she dealt with; and (2) to introduce aspects that helped her become resilient within that stressful circumstance. The results indicated that curriculum changes had largely contributed to the participant's stress. The key features that aided her to tackle day-to-day problems as a teacher include supportive institution and conducive social relationships. Additionally, the teacher appeared to have a strong positive emotion as influenced by people around her, e.g. her students. These findings could contribute to better understanding of how the negative effects of stress can be reduced by promoting key features of resilience, particularly in the Indonesian teaching context. As a conclusion, several key findings were highlighted followed by a recommendation for further research.